Memorandum of Understanding between Guangxi Minzu Normal University And Universiti Teknologi MARA - Cawangan Kelantan, UiTM (2022)
This Memorandum of Understanding between the Guangxi Minzu Normal University of China and Universiti Teknologi MARA of Malaysia reflects consensus resulting from the mutual covenant between the leaders of these institutions. We, the undersigned, have corresponded in our eagerness to examine the possibility of forming a partnership focusing on various areas of mutual cooperation. Following discussions between us, we agree to explore these goals at our respective institutions.